VHDL BEHAVIORAL MODEL - Shandilya, Shivangi; Sangwan, Surekha; Yadav, Ritu (IJRDO -Journal of Computer Science Engineering, 2015)
The language constructs introduced so far allow hardware to be described at a relatively detailed level. Modeling a circuit with logic gates and continuous assignments reflects quite closely the logic structure of the circuit being modeled; however, these constructs do not provide the power of abstraction necessary for describing complex high level facets of a system. The procedural constructs described in this chapter are well suited to tackling problems such as describing a microprocessor or implementing complex timing checks. With the increasing complicacy of digital design, it has become vitally important to make wise design decisions early in a project. Designers need to be able to evaluate the trade-off of various architectures and algorithms before they decide on the optimum architecture and algorithm to device in hardware